The Impact of Work Family Conflict on Female Teacher’s Intention to Leave the Job a Survey of Female Teaching Staff in Public Sector Colleges - Sultan, Sarwat; Jeganatha, Sureen; Sameem, MAM; Hamzah, Imaduddin (Politeknik Ilmu Pemasyarakatan, 2023)
As we all know that education is a serious issue in the development of any country. The purpose of this study is to find the impact of work-family conflict on female teacher’s intention to leave the job in the education sector and estimate that how difficulties influence the personal and professional life of female teachers. The study focused on 3 dimensions of work-family conflict such as: heavy teaching load, work timing and mental health issues which influence female teachers to leave the job. A Sample of 198 respondents was taken under this study, while the data is collected through the questionnaire tool. Data is examined with the help of SPSS software and Microsoft excel. The finding discloses that mental health issues influence female teachers to leave the job and cause negative impact on their personal and professional life and also affected their performance were as work timing and heavy teaching load results show neutral behavior of female towards the statement.